Knowledge Marketplaces: An Analysis of the Influence of Business Models on Instructors’ Motivations and Strategies - Cisel, Matthieu Tenzing; Pontalier, David (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
Unlike MOOC platforms such as Coursera or edX, which typically partner with institutions of higher education, online knowledge marketplaces allow anyone to broadcast courses and charge for them. In this article, we investigate, through a mixed-method approach, the motivations and strategies of the instructors of Udemy and Skillshare. Semi-structured interviews and a quantitative analysis of the characteristics of Skillshare’s courses, obtained using a Web scraper, suggest that while a significant proportion of the marketplace’s instructors are outreach driven, the majority are income driven. They develop strategies to maximize their revenues, notably by adapting the characteristics of their courses, such as the number of videos, to the business model of the platform. Courses are shorter on Skillshare than on Udemy, where instructors’ incomes are proportional to the number of registrations. We hypothesize that the latter platform’s business model incentivizes instructors to create longer courses in order to attract wider audiences.